TREND OF AIR TEMPERATURE IN THE STATE OF PARANÁ, BRAZIL (TENDÊNCIA DA TEMPERATURA DO AR NO ESTADO DO PARANÁ, BRASIL) - Gabriela Leite Neves (Revista Brasileira de Climatologia, 2016)
Considering the importance of climatologic series and the local temperature variability analyses, this study aimed to evaluate the trend of maximum and minimum air temperature in the State of Paraná, Brazil. It were used daily data for the period 1980 to 2009 of 28 locations. The trend magnitude was obtained through linear regression and statistical significance using the Mann-Kendall non-parametric test. The spatial distribution of changes found was represented in geo-referenced maps elaborated through the ARCGIS v.10.0 with the spline interpolation method. The results revealed that the State of Paraná presents great variability in air temperature changes, with differences between places ranging from reductions of 0.5 reductions to increases of 0.6 °C/decade. These increases occurred mainly during the winter and the spring and reductions in the autumn. It was not possible to define simultaneity between the trends due to different changes found, which may be related to local factors such as relief, vegetation and regional activities.